5‐Hydroxytryptamine type 7 receptor neuroprotection against NMDA‐induced excitotoxicity is PDGFβ receptor dependent. (13th February 2013) - Vasefi, Maryam S.; Kruk, Jeff S.; Heikkila, John J.; Beazely, Michael A.
Abstract The serotonin (5‐HT) type 7 receptor is expressed throughout the CNS including the hippocampus. Long‐term (2–24 h) activation of 5‐HT7 receptors regulates growth factor receptor expression, including the expression of platelet‐derived growth factor (PDGF) β receptors. Direct activation of PDGFβ receptors in primary hippocampal and cortical neurons inhibits NMDA receptor activity and attenuates NMDA receptor‐induced neurotoxicity. Our objective was to investigate whether the 5‐HT7 receptor‐induced increase in PDGFβ receptor expression would be similarly neuroprotective. We demonstrate that 5‐HT7 receptor agonist treatment in primary hippocampal neurons also increases the expression of phospholipase C (PLC) γ, a downstream effector of PDGFβ receptors associated with the inhibition of NMDA receptor activity. To determine if the up‐regulation of PDGFβ receptors is neuroprotective, primary hippocampal neurons were incubated with the 5‐HT7 receptor agonist, LP 12, for 24 h. Indeed, LP 12 treatment prevented NMDA‐induced neurotoxicity and this effect was dependent on PDGFβ receptor kinase activity. Treatment of primary neurons with LP 12 also differentially altered NMDA receptor subunit expression, reducing the expression of NR1 and NR2B, but not NR2A. These findings demonstrate the potential for providing growth factor receptor‐dependent neuroprotective effects using small‐molecule ligands of G protein‐coupled receptors.